Microbial loads on selected fresh blueberry packing lines. (June 2019) - Gazula, Himabindu; Quansah, Joycelyn; Allen, Renee; Scherm, Harald; Li, Changying; Takeda, Fumiomi; Chen, Jinru
Abstract: Foodborne outbreaks have been linked to the consumption of blueberries contaminated with pathogenic bacteria. The microbial quality of blueberries could be influenced by the conditions of hygiene prevailing during post harvest handling. This study evaluated the hygienic conditions of 6 selected fresh blueberry packing lines. Five of the packing lines were sampled twice and the remaining one was sampled once during the summer of 2015 and the summer of 2017. A delimited area (100 cm 2 ) on each of the ten selected sites of the packing lines was swabbed with sterile sponges before the packing started (AM samples), during lunchtime break (NOON samples), and at the end of a packing day (PM samples). The sponges were thoroughly rinsed with Dey-Engley neutralization broth which was subsequently sampled for total aerobes, yeasts and molds, total coliforms, fecal coliforms, and enterococci. Results showed that sample site and sampling time had a significant influence ( P ≤ 0.05) on total aerobic, yeast and mold, and total coliform counts. The PM samples had significantly higher ( P ≤ 0.05) total aerobic and yeast and mold counts than the NOON samples which had significantly higher ( P ≤ 0.05) counts than the AM samples. Fourty-six out of the 310 (14.8%) collected samples tested positive for enterococci while 27 (8.7%) samples tested positive for fecal coliforms. Berry lugs, rubber belts on color sorters, and premature berry disposing areas had significantly higher ( P ≤ 0.05) microbial counts than the other sites. The study suggests that some sites along fresh blueberry packing lines could become contaminated by microorganisms during packing. Whether these contaminated sites will become a food safety concern depends on the incidence of pathogen presence in the microbial community and efficacy of routine sanitizing treatments. Highlights: Hygiene conditions of six fresh blueberry packing lines were evaluated. Most sampled packing lines had acceptable hygiene conditions before packing started. Microbial counts on packing lines increased significantly as packing proceeded. Belt on color sorter and berry lug had higher microbial loads than other sites. Twenty-seven of the 310 sampled sites (8.7%) tested positive for fecal coliforms.